The Effects of Internet Addiction Disorder on Students' Learning Motivation - Mulia Sosiady; Nasrullah Djamil; Ermansyah Ermansyah (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research was conducted at the Management S1 Study Program of UIN Suska Riau and the S1 Management Study Program of UIN Sunan Gunung Djati Bandung. This study used a comparative method comparing two symptoms on different objects, in this study the number of samples was 96 respondents, each 48 samples were students. S1 Management study program at UIN Suska Riau and 48 samples were students from the S1 Management study program at UIN Sunan Gunung Djati Bandung, R2 (R Square) students in Management S1 study program 0.490 or 49% and R2 (R Square) students in UIN Management S1 study program Sunan Gunung Djati Bandung. The suggestion in this study is that UIN Suska Riau students should be wiser in using internet facilities and it is better if the internet addiction of UIN Bandung students is used to increase learning motivation and for business activities such as online business which is very interesting in business prospects in the current digitalization era.